Evaluation of Paracoccidioides brasiliensis exoantigen in the detection of delayed dermal hypersensitivity in experimental and human paracoccidioidomycosis - Marques, M. [UNESP]; Soares, A. [UNESP]; Franco, M. [UNESP]; Camargo, Z. P.; Marques, S. [UNESP]; Memoes, R. P. [UNESP]; Souza, L. R. [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP] (Oxford University Press (OUP), 1996)
The exoantigen of Paracoccidioides brasiliensis standardized by Camargo et al. [1] (AgR) was used to evaluate the in vivo and in vitro cell immune response of experimental animals and of patients with paracoccidioidomycosis (PBM). Fava Netto antigen (AgF) was tested in parallel as a control antigen. The study was conducted with mice and guinea pigs infected with P. brasiliensis or immunized with its fungal antigens, on patients with PBM and on their respective control groups. The cell immune response was analysed by skin tests, and by the macrophage and leucocyte migration inhibition tests (MMIT and LMIT) in the animals and in the patients, respectively. The skin test with AgR as paracoccidioidin was positive in infected or immunized mice and guinea pigs and negative in control animals. The skin tests with AgR (24 h) showed 96.7% positivity in patients with PBM and were negative in control individuals. Histopathological study of the in vivo tests in the different experimental models was consistent with a delayed hypersensitivity response (DHR). Immunohistochemical study of the skin tests of PBM patients demonstrated a predominance of T lymphocytes, confirming the nature of a DHR to the fungal antigens. The in vitro cell immune response showed variable results for the various experimental models, i.e. significant rates of MMIT in immunized mice, a tendency to positivity in infected guinea pigs, and the absence of migration inhibition in PBM patients. Taken together, the data indicate that the AgR is efficient as paracoccidioidin in the evaluation of DHR in PBM, with an optimum time of reading the test of 24 h.
Keywords: Paracoccidioides brasiliensis; paracoccidioidin; paracoccidioidomycosis; fungus antigen; allergenicity; animal experiment; animal model; antigen detection; delayed hypersensitivity; guinea pig; immune response; macrophage migration; male; mouse; nonhuman; paracoccidioides brasiliensis; skin allergy; skin test; south american blastomycosis; t lymphocyte activation; Animals; Antigens, Fungal; Dermatitis, Allergic Contact; Guinea Pigs; Humans; Immunity, Cellular; Lymphocytes; Macrophages; Male; Mice; Paracoccidioides; Paracoccidioidomycosis; Reference Values; Skin; Skin Tests; Animalia; Cavia; Cavia porcellus; Fava; Fungi; paracoccidioidomycosis brasiliensis; Sus scrofa